Increment in hemoglobin and hematocrit levels after blood transfusion in a tertiary care hospital (Journal of Pathology of Nepal, 2022)
Background: Blood transfusion is considered to be the first line of therapy for all types of anemia. One unit of blood transfusion is known to increase the hemoglobin level by 1g/dl and hematocrit by 3%. This study aims to analyze the mean increment in hemoglobin and hematocrit levels after 1-unit of blood transfusion in a tertiary care hospital.Materials and Methods: A retrospective study was done. 133 patients with 1-unit of blood transfusion (whole blood or packed red blood cells)having pre and post-transfusion hemoglobin and hematocrit values were enrolled in the study.Results: Patients of all diagnoses, who received blood transfusion were enrolled, with the highest proportion (27.1%) in the age group 18-35 years. Male predominance was seen (57.1%) and a majority of the patients were on hemodialysis (57.9%). The most common blood group was B positive (30%) and 90.9% were Rh positive. 48 patients were transfused with whole blood and 85 were transfused with packed red blood cells. The mean increment in hemoglobin and hematocrit levels were 0.75 ± 2.21 and 2.47 ± 6.84 respectively. A significant increment in post-transfusion parameters was seen compared with pre-transfusion parameters (p